Automated processing of measuring information and control processes of eutrophication in water for household purpose, based on artificial neural networks - Безвесільна, О.М.; Єльнікова, Т.О.; Подчашинський, Ю.О. (Proceedings of National Aviation University, 2006)
The possibilities of application informational-computer technologies for automated handling of a measuring information about development of seaweed (evtrofication) in household reservoirs are considered. The input data’s for a research of processes evtrofication are videoimages of tests of water, which are used for the definition of geometric characteristics, number and biomass of seaweed. For handling a measuring information the methods of digital handling videoimages and mathematical means of artificial neural networks are offered.